Exploring Institutional Language Policies Pertaining to the Provision of Mental Health Services to Inuit in Nunavut - Duncan, Alana (Université d'Ottawa / University of Ottawa, 2021)
In 2019, Statistics Canada reported that the death by suicide rate among Inuit in Canada was approximately nine times higher than that of their non-Indigenous counterparts. This alarming statistic reflects the ongoing impact of colonial legacy on Inuit society, which has been characterized as cultural genocide and linguicide (TRC, 2015). In the last two decades, various organizations have taken up efforts to help heal communities, however there is little research examining what makes those efforts effective, and virtually none that has addressed the place of language within mental health programming. Yet, language is a pillar of Inuit health and wellness (ITK, 2016). This thesis explores institutional language policies pertaining to the provision of mental health services to Inuit in Nunavut from a decolonial perspective. I conduct a document review and six semi-structured interviews to examine which government-funded mental health programs provide services in the Inuit Language, the challenges they face in doing so, and solutions that they may envision. Applying decolonization as both my conceptual and methodological framework, I conduct a thematic analysis of both documents and interviews, as well as a critical discourse analysis combining both sets of data. The results of this study reveal that mental health service providers serving Nunavut largely have de facto language policies. They attribute challenges to offering Inuit Language programming to the dominance of English, hiring practices and funding models. However, it is demonstrated both in documents and by study participants that organizations have found holistic and inclusive ways to not only offer programming in the Inuit Language, but also encourage and increase its use. Local and cultural knowledge prove to be indispensable in understanding systemic challenges to Inuit Language provision in mental health services, as well as how they can be remediated.